Biomarkers in exposure-based treatment of anxiety in virtual reality: a systematic review - Ernst, Mathias Torp; Hyldig Nielsen, Jakob; Runge, Eik; Bouchard, Stéphane; Clemmensen, Lars (Frontiers in Virtual Reality, 2024)
Background: A large proportion of individuals with anxiety-related disorders refrain from seeking treatment. This may be because traditional exposure treatments induce anxiety. However, advances in exposure using virtual reality (VR) technology may encourage more individuals to seek treatment. Furthermore, using biomarkers with VR-based exposure may enable clinicians to assess anxiety levels objectively and collect data in a naturalistic setting. Methods: Here, we conduct a systematic review of the literature on the use of biomarkers in VR-based exposure treatment for anxiety. Twenty-seven studies were included, with a total of 1046 participants. Results: We found that heart rate was the only biomarker that tentatively could identify changes within (75% of instances) and between sessions (60% of instances). The levels of synchrony between the findings for overall biomarkers and the results from questionnaires showed inconclusive results. Regarding the levels of synchrony between the findings for particular biomarkers and the results from questionnaires, only skin conductance level was highly synchronous for differences between groups (87% of instances). Conclusions: Based on the present review, biomarkers cannot yet be used reliably to distinguish differences in self-reported symptoms of anxiety in VR-based exposure treatments.